Design of Ti4+-doped Li3V2(PO4)3/C fibers for lithium energy storage. Issue 6 (15th March 2022) - Huang, Zan; Luo, Peifang; Zheng, Honghong
Abstract: In this work, we propose a facile approach to fabricate Ti 4+ -doped Li3 V2 (PO4 )3 /C (abbreviated as C-LVTP) nanofibers using an electrospinning route followed by a high temperature treatment. In this designed nanocomposite, the ultrafine LVTP dots are homogeneously dispersed into one-dimensional carbon nanofibers and the Ti 4+ doping does not destroy the crystal structure of monoclinic Li3 V2 (PO4 )3 . Compared to the undoped Li3 V2 (PO4 )3 /C (abbreviated as C-LVP), the as-fabricated C-LVTP fibers present higher reversible capacity, superior high-rate capability as well as better cyclic property. Especially, the C-LVT7% P cathode delivers not only high capacities of 187.2 and 160.3 mAh g −1 at 0.5 and 10 C respectively, but also stable cyclic property with the reversible capacity of 135.8 mAh g −1 at 20 C following 500-cycle spans. The good battery characteristics of C-LVT7% P can be mainly ascribed to Ti 4+ doping, which can increase the electrical conductivity and Li + diffusion coefficient.